2014
DOI: 10.1016/j.jchf.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Physician Continuity Improves Outcomes for Heart Failure Patients Treated and Released From the Emergency Department

Abstract: Early follow-up after an ED visit is associated with better outcomes, particularly if conducted with a familiar physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…We have previously shown that follow-up in the first month after a hospitalization or emergency department (ED) visit for HF with physicians familiar with that patient is associated with lower rates of subsequent hospitalization or ED visits over the next 6 months than early follow-up with another physician. 6,7 However, it is unknown whether continuity of care within the first 2 weeks after a hospitalization/ED visit influences outcomes in the 30-day timeframe emphasized in the Affordable Care Act. We included patients who were seen in an ED and those discharged from the hospital because up to one third of HF exacerbations in Alberta are treated and released from the ED.…”
Section: See Clinical Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that follow-up in the first month after a hospitalization or emergency department (ED) visit for HF with physicians familiar with that patient is associated with lower rates of subsequent hospitalization or ED visits over the next 6 months than early follow-up with another physician. 6,7 However, it is unknown whether continuity of care within the first 2 weeks after a hospitalization/ED visit influences outcomes in the 30-day timeframe emphasized in the Affordable Care Act. We included patients who were seen in an ED and those discharged from the hospital because up to one third of HF exacerbations in Alberta are treated and released from the ED.…”
Section: See Clinical Perspectivementioning
confidence: 99%
“…We included patients who were seen in an ED and those discharged from the hospital because up to one third of HF exacerbations in Alberta are treated and released from the ED. 7 …”
Section: See Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that (in Canada) early follow-up after a hospitalization or emergency department visit for heart failure with physicians familiar with a particular patient is associated with lower readmission rates than early follow-up with any physician. 4,5 Are the investigators able to determine what proportion of early follow-up appointments in Get With The Guidelines-Heart Failure hospitals were planned to be with a physician who had been involved with the patient's care either before or during the index hospitalization? We think that continuity of care is one of the fundamental building blocks for any high-performing healthcare system and that the current guideline's emphasis on prompt follow-up after hospitalizations or emergency department visits may lead to system changes that neglect the importance of continuity.…”
Section: To the Editormentioning
confidence: 99%
“…25 In a recent retrospective study of more than 12,000 patients treated and discharged from the ED for HF, the rate of death or all-cause hospitalization at 6 months was 11% lower in those who saw a familiar physician in the first month versus those with no outpatient visits, and 15% lower than those with visits only with unfamiliar physicians. 26 …”
Section: Outpatient Providersmentioning
confidence: 99%